Volumetric analysis of extraction sockets using cone beam computed tomography: a pilot study on ex vivo jaw bone - Jimoh Olubanwo Agbaje (Blackwell Synergy, 2007)
Aim: The aim of this study was to determine the accuracy of volumetric analysis of extraction sockets using cone beam computed tomography (CBCT). Material and Methods: The volume of 40 dental alveoli in nine dry skull specimens (four mandibles and five maxillae) was determined by measuring the volume of the tooth socket impression using the water displacement technique. This was considered as the gold standard. Then, the tooth socket was scanned with CBCT and data were uploaded in the semi-automated Livewires segmentation software. The software segments the tooth socket in consecutive 1 mm-thick two-dimensional slices. After segmentation, the total volume of the delineated socket was computed. The statistical difference between direct volumetric measurements and those obtained with CBCT imaging was assessed using the Student paired t-test. Result: The mean socket volume of the skull specimens was 227 91mm3 when obtained by direct measurement and 225 90mm3 when obtained by CBCT imaging. Student paired t-test showed no significant differences between both volume measurements (p40.1). Conclusions: CBCT permits imaging of anatomical structures in three planes and allows for reliable volume estimates. The results should be verified in clinical circumstances and might have potential applicability for evaluation of extraction socket healing under different conditions.